Basic systems for public budgets, with reference to the budget model in egypt and jordan - Taher, Mirkhas; Al-safar , Ahmed (Humanities Journal of University of Zakho, 2023)
There is a need for a theoretical existence or a group of theories that enable us to understand the field related to public budgets and the basis that directs their development as well as the extent of their impact in dealing with existing problems. Budgets are prepared using a formal structure that links the different budget components into a coherent document. This structure provides the foundation that guides budget development and, as a more appropriate name, we will call it "budget systems". Although terms such as “budget formulas”, “budget methodologies” and “types of budgets” are often used, “budget systems/systems” seem more appropriate, because as with any system, budgets are also a formal structure with components. Interconnected which are linked together in a coherent manner to achieve the goals and objectives of the government. The study aims to identify all types of basic public budget systems that exist from the items budget system to other modern and developed systems, and to delve into a detailed review of them and explain their structures, as well as how to build them in order to give a complete picture of each of its types, as well as shed light on the budget system in each of Egypt And Jordan in order to benefit from their experience in an effort to develop the system of public budgets by the competent authorities in developing countries. The study reached several results, the most important of which can be summarized as follows: - The use of budget items is prevalent among the governments of developing countries, such as the majority of Arab countries, including Iraq as well, and we can exclude Jordan, which has recently sought to develop its financial system, including the general budget. - There is a possibility for the financial authorities and public budget departments in developing countries, including Arab ones, to develop their public budget systems by introducing new amendments, as well as using the structures of modern and developed systems, in order to better allocate economic resources and thus achieve better levels of growth and economic development, and this is what achieves the hypothesis of the study Here, one can benefit from Jordan's experience. Based on the results reached, several recommendations were made, the most important of which are the following: - The financial authorities, as well as the authority concerned with the public budget in developing countries, including Iraq, must also pay more attention to the developments of public budget systems in the world and strive to reach the use of the best budget system that achieves macroeconomic goals, especially those related to social aspects such as poverty and inequality in the distribution of income. . - The Iraqi general budget authority (the budget department - the Ministry of Finance) should form a special team of specialists in order to look into the modern budget systems and then decide to update the existing system and try to prepare the concerned employees in order to better allocate the financial and economic resources of the country.